A two-antenna single RF front-end DOA estimation system for wireless communications signals - Görçin, Ali; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers, 2014)
Both adaptive beamforming methods and interference management systems improve the capacity of wireless communications systems, however they may require direction of arrival (DOA) information of signals. On the other hand, most of the DOA estimation systems suffer from computational complexity, high costs, and bulky size which prevents mobility. Antenna array inflexibility of DOA estimation systems also prevents prevalence over the whole wireless spectrum. In this paper, a solution to these problems which benefits from the advantages of switched antenna systems along with the time-variant sequential sampling process is proposed: a two-antenna, single radio-frequency (RF) front-end DOA estimation system which extends the measurements to different locations by shifting the antenna tuple together as a single entity. The system adjusts the antenna spacing for adaptive spectrum coverage. An extension to total measurement time is introduced, however, when compared to DOA estimation systems which have separate RF front-end for each antenna, the system has moderate complexity and size. A measurement setup is developed and performance of the proposed system is provided for extensive set of wireless standards and measurement parameters. Multiple signal classification is selected as DOA method for the proposed system and the DOA estimation performance is compared with the pseudo-Doppler system.
WOS: 000343608600040
Keywords: Music; Sequential Sampling; Signal Direction of Arrival Estimation; Switched Antenna Systems; Wireless Communications; Wireless Standards